What do teachers need? An exploration of evidence-informed practice for classroom assessment in Ontario. Issue 2 (3rd April 2017) - Cooper, Amanda; Klinger, Don A.; McAdie, Patricia
Abstract: Background: Within the realm of public education, there is a well-known 'knowledge to practice gap' on current conceptions of classroom assessment. A collaborative research project undertaken by the Elementary Teachers' Federation of Ontario (ETFO) and a research team at Queen's University explored the roots of this gap from the perspectives of practising educators. Purpose: The primary purpose of this research project was to understand better the ways in which teachers access and incorporate emerging, research-informed conceptions and practices related to classroom assessment. Our intention was to integrate our findings from teachers with the current research literature to identify challenges and opportunities, and to provide direction for more effective communication strategies for the teaching profession. Programme description: The research project was part of a larger initiative (the Knowledge Network for Applied Education Research based in Ontario, Canada). This initiative seeks to increase research use and its impact (efforts called Knowledge Mobilisation (KMb) in Canada) in the public education system (ages 5 to 18, grades kindergarten to 12) through collaborative partnerships among research producers and users. Research questions: Three research questions provided the foundation for our efforts to address the primary purpose of our research project. (1) What are the methods in which teachers obtain current and emerging knowledge regarding classroom assessment? (2) What is the evaluative process teachers use to judge and incorporate research knowledge into their assessment practices? (3) What methods can be used to better communicate sound research knowledge regarding classroom assessment to practising teachers? Data collection and analysis: Data was collected through a series of three-day Summer Institutes sponsored by the ETFO. A selection of 76 elementary teachers each participated in one of 10 focus groups. Each focus group lasted between 60 and 90 min. Data from the focus groups were analysed qualitatively. Findings: Consistent with existing literature in related fields, we found that teachers predominantly acquire information about assessment practices from other teachers, rather than from research. These teachers noted challenges in finding the time to access current research, along with issues of ease of access and comprehensibility. Strong networks and leadership structures to filter research, in order to integrate the research into evidence-based assessment practices, were reported as valuable ways of finding and judging current research. Lastly, teachers provided suggestions to increase the uptake of research-related assessment products including research summaries, videos, engaging websites, professional readings, and (most importantly) opportunities to share ideas with colleagues. Conclusions: For teachers to build capacity about assessment literacy and evidence-informed practices, they require time, training, and credible filters to comprehend the research and transform assessment evidence into guidelines to operationalise in practice.